Large distal tibia osteochondroma with deformed fibula: Excision and anatomical reconstruction of ankle syndesmosis - Goh, Kian Liang; Mohammad Amin, Mohammad Azril; Sharifudin, Mohd Ariff; Anwarali Khan, Mohammed Harris (2016)
INTRODUCTION Osteochondroma is a benign cartilaginous disease of the bone. Its exophytic growth can occasionally result in periarticular deformity and pain. We describe a case of large osteochondroma of the lateral malleolus causing deformity and pain in a growing child.